Modulation of Human Mesenchymal Stem Cell Immunogenicity through Forced Expression of Human Cytomegalovirus US Proteins - Soland, Melisa A. (Public Library of Science, 2012)
BACKGROUND: Mesenchymal stem cells (MSC) are promising candidates for cell therapy, as they migrate to areas of injury, differentiate into a broad range of specialized cells, and have immunomodulatory properties. However, MSC are not invisible to the recipient's immune system, and upon in vivo administration, allogeneic MSC are able to trigger immune responses, resulting in rejection of the transplanted cells, precluding their full therapeutic potential. Human cytomegalovirus (HCMV) has developed several strategies to evade cytotoxic T lymphocyte (CTL) and Natural Killer (NK) cell recognition. Our goal is to exploit HCMV immunological evasion strategies to reduce MSC immunogenicity. METHODOLOGY/PRINCIPAL FINDINGS: We genetically engineered human MSC to express HCMV proteins known to downregulate HLA-I expression, and investigated whether modified MSC were protected from CTL and NK attack. Flow cytometric analysis showed that amongst the US proteins tested, US6 and US11 efficiently reduced MSC HLA-I expression, and mixed lymphocyte reaction demonstrated a corresponding decrease in human and sheep mononuclear cell proliferation. NK killing assays showed that the decrease in HLA-I expression did not result in increased NK cytotoxicity, and that at certain NK∶MSC ratios, US11 conferred protection from NK cytotoxic effects. Transplantation of MSC-US6 or MSC-US11 into pre-immune fetal sheep resulted in increased liver engraftment when compared to control MSC, as demonstrated by qPCR and immunofluorescence analyses. CONCLUSIONS AND SIGNIFICANCE: These data demonstrate that engineering MSC to express US6 and US11 can be used as a means of decreasing recognition of MSC by the immune system, allowing higher levels of engraftment in an allogeneic transplantation setting. Since one of the major factors responsible for the failure of allogeneic-donor MSC to engraft is the mismatch of HLA-I molecules between the donor and the recipient, MSC-US6 and MSC-US11 could constitute an off-the-shelf product to overcome donor-recipient HLA-I mismatch.